(untitled) (Bangladesh Agronomy Journal, 2020)
An experiment was conducted at Agronomy Research Field of Bangladesh Agricultural Research Institute, Gazipur for five consecutive years (2014-2015 to 2018-2019) to establish a functional relationship between grain yield and spikes/m2 of wheat at late sown condition. Variation of spikes/m2 was created by five seed rates (90, 120, 150, 180 and 210 kg/ha). Pooled average value of spikes / m2 was observed the highest (479-506) in 180-210 kg seed /ha. From the structural treatment, the highest grain yield (pooled average of 3876-4153 kg/ha ranged 3295-5028 kg/ha) of wheat was produced in the seed rate of 150-180 kg/ha. The estimated optimum seed rate was found 162.29 kg/ha with the estimated grain yield 3989 kg/ha of wheat at late sown condition through the developed function model of Y=485.91+43.17X-0.133X2 (R2=0.87). Again, the estimate optimum spikes/m2 was noticed 423 when the estimated grain yield of wheat was 4135 kg/ha at late sown condition through the developed functional model of Y=-2837+32.98X-0.039X2 (R2=0.83). The grain yield would be increased about 13% as compared to recommended seed rate (120 kg/ha) of wheat. Spikes / m2 had significant positive correlation with seed rate (r=0.79 at p=0.05) of wheat. Relationship between observed grain yield and predicted grain yield (when relationship between spikes/m2 and grain yield) showed a good consistency (Y=1.0006X, R2=0.94 and r = 0.97 at p<0.01). From the results of the study it is concluded that 162 kg/ha of seed rate and 423 spikes / m2 would be optimum for maximum yield) 4135 kg/ha) of wheat at late sown condition. Bangladesh Agron. J. 2019, 22(1): 105-113